2020
DOI: 10.1016/j.cub.2019.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Wave Promotes Cell Extrusion

Abstract: Highlights d Calcium wave propagates from extruding cells within the epithelium d Calcium wave promotes apical extrusion of transformed or apoptotic cells d IP 3 R, gap junction, and TRPC1 are involved in calcium wave d Calcium wave induces polarized movement of surrounding cells toward extruding cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 35 publications
1
69
0
Order By: Relevance
“…Importantly, the mechanism we characterised in this study are conserved in mammals as similar ERK dynamics were observed near dying MCF10A cells which also generate transient resistance to apoptosis (personal communication, Olivier Pertz lab). Interestingly, other reports also described Ca 2+ and ERK activation waves emanating from extruding MDCK pretumoral cells or caspase-induced MDCK extrusion 18,19 . However in these cases the waves rather promote extrusion of the dying/extruding cells through collective convergent movements.…”
mentioning
confidence: 94%
“…Importantly, the mechanism we characterised in this study are conserved in mammals as similar ERK dynamics were observed near dying MCF10A cells which also generate transient resistance to apoptosis (personal communication, Olivier Pertz lab). Interestingly, other reports also described Ca 2+ and ERK activation waves emanating from extruding MDCK pretumoral cells or caspase-induced MDCK extrusion 18,19 . However in these cases the waves rather promote extrusion of the dying/extruding cells through collective convergent movements.…”
mentioning
confidence: 94%
“…This design can confer stringency, so that extrusion is only triggered when an apoptotic event is clearly underway. It will therefore be interesting to see how this system for RhoA activation cooperates with other signals [32] and cytoskeletal regulators [9] to ensure that epithelia can rapidly eliminate apoptotic cells by apical extrusion.…”
Section: Supplementarymentioning
confidence: 99%
“…Calcium wave and collective movements during cell extrusionAdapted from[15]. A: Cell extrusion is triggered in MDCK cells or zebrafish either by a transformed RasV12 cells surrounded by WT (EDAC) or through overexpression of Caspase-8.…”
mentioning
confidence: 99%